Targeted removal of trichlorophenol in water by oleic acid-coated nanoscale palladium/zero-valent iron alginate beads - Chang, Jaewon; Woo, Heesoo; Ko, Myoung-Soo; Lee, Jaesang; Lee, Seockheon; Yun, Seong-Taek; Lee, Seunghak (ELSEVIER, 2015)
A new material was developed and evaluated for the targeted removal of trichlorophenol (TCP) from among potential interferents which are known to degrade removal activity. To achieve TCP-targeted activity, an alginate bead containing nanoscale palladium/zero-valent iron (Pd/nZVI) was coated with a highly hydrophobic oleic acid layer. The new material (Pd/nZVI-A-O) preferentially sorbed TCP from a mixture of chlorinated phenols into the oleic acid cover layer and subsequently dechlorinated it to phenol. The removal efficacy of TCP by Pd/nZVI-A-O was not affected by co-existing organic substances such as Suwannee River humic acid (SRHA), whereas the material without the oleic acid layer (Pd/nZVI-A) became less effective with increasing SRHA concentration. The inorganic substances nitrate and phosphate significantly reduced the reactivity of Pd/nZVI-A, however, Pd/nZVI-A-O showed similar TCP removal efficacies regardless of the initial inorganic ion concentrations. The influence of bicarbonate on the TCP removal efficacies of both Pd/nZVI-A and Pd/nZVI-A-O was not significant. The findings from this study suggest that Pd/nZVI-A-O, with its targeted, constant reactivity for TCP, would be effective for treating this contaminant in surface water or groundwater containing various competitive substrates. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CATALYTIC HYDRODECHLORINATION; REDUCTIVE DECHLORINATION; 2,4,6-TRICHLOROPHENOL; CHLOROPHENOLS; NANOPARTICLES; 2,4-DICHLOROPHENOL; KINETICS; PD/FE; PENTACHLOROPHENOL; BIODEGRADATION